"Society Wants to See a True Victim": Police Interpretations of Victims of Sexual Violence. (April 2021) - Ricciardelli, Rosemary; Spencer, Dale C.; Dodge, Alexa
Despite attempts to rectify the injustices experienced by victims of sexual violence within the criminal justice system, unfounded rates for sexual violence remain high and many victims continue to feel disempowered and voiceless. In this context, police officers wrestle with how to support victims, while protecting those who may be falsely accused and grappling with deeply imbedded cultural beliefs about who constitutes a "true" victim. In the current article, we draw on interviews with officers working in Internet Child Exploitation, sex crimes, and child abuse units across 10 Canadian police service organizations to understand how police interpret and respond to child, youth, and adult victims of sex crimes. We unpack the range of interpretations of victims, explore if and how interpretations of victims translate into police perceptions of their interactions with victims, and their interpretations of the possible outcomes that can be offered in the investigation. We highlight the difficulties officers encounter as they strive to balance their occupational role with victims' needs. We argue that police interpretations of sexual violence and sexual violence victims are shaped by the officer's adherence to or rejection of understandings of the "ideal victim".